Polymeric ionic liquids and MXene synergistically improve proton conductivity and mechanical properties of polybenzimidazole-based high-temperature proton exchange membranes. (19th March 2023) - Yu, Di; Cui, Yinghe; Wang, Shuang; Wang, Xiaodong; Yong, Zhipeng; Sun, Han; Wang, Xiaorui; Li, Chenglong; Pan, Feng; Wang, Zhe
Abstract: A series of Polymeric ionic liquids (PILs) cross-linked amino polybenzimidazoles with MXene fillers were successfully prepared. By anion replacement of PILs, the OH − of the system can interact with phosphoric acid (PA) to form H2 PO4 − and HPO4 2− to transfer protons, and the hydroxide existing on the surface of MXene is also conducive to the transfer of protons. Therefore, the synergistic effect of the two enables the membrane to have high proton conductivity with low PA absorption. Through the covalent cross-linking between PILs and PBI and the interaction between the oxygen-containing groups on the surface of MXene and the = N and –NH of imidazole, so the mechanical performance can be greatly improved. The proton conductivity of AmPBI-PIL-5-MXene-3 can reach 91.4 mS cm −1 at 180 °C, which is twice that of pristine AmPBI. Moreover, the tensile stress after PA doping can reach 11.1 MPa, which is twice that of pristine AmPBI. Meanwhile, the power density of AmPBI-PIL-5-MXene-3 can reach 219 mW cm −2 at 350 mA cm −2, which is 1.8 times that of pristine AmPBI. In addition, there is no voltage loss after 100 h test at 160 °C and 200 mA cm −2, which indicates the excellent stability of the membrane. Graphical abstract: Image 1 Highlights: PIL and MXene can improve mechanical properties and proton conductivity. The synergistic effect of PIL and MXene enhances performance. The prepared cross-linked composite membrane has excellent fuel cell performance. MXene plays a key role in enhancing the tensile strength of the membranes.